Dance! dance! underpants! - Shea, Bob (Shea, Bob. Ballet Cat., 2016)
Ballet Cat and her friend Butter Bear have practiced a dance to perform for an audience, but Butter Bear will need a lot of encouragement to try the super high leaps.